Undergraduates’ Perception of Factors Influencing Cybercrimes in Selected Universities in Anambra State, South-East, Nigeria - Okeke, Obinna Chukwudalu; Oli, Nneka Perpetua (Practicum Psychologia, 2024)
This study examined undergraduates’ perception of factors influencing cybercrimes in selected universities in Anambra State, South-East, Nigeria. study adopted mixed methods research design. The area of study comprised of public and private universities in Anambra State. The scope of the study is on investigating perception of undergraduates’ involvement in cybercrimes in selected universities in Anambra State, South-East, Nigeria. The target population was 40,092 undergraduate regular students of Nnamdi Azikiwe University, Awka, Paul University Awka, Tansian University, Umunya and Chukwuemeka Odumegwu Ojukwu University, Igbariam who were 16 years and above. The sample size for this study was 1,083 undergraduates was generated using Taro Yamane statistical method of sample size determination, while 20 participants were selected through purposive and snowball sampling techniques for the In-Depth Interview (IDI) session. The research used both probability and non probability sampling methods in the selection of respondents. Multi-stage sampling procedure which involved the use of different sampling techniques in the selection of respondents was employed in the study. Questionnaire and IDI guide were the quantitative and qualitative instruments used for data collection in the study, respectively. Data collected through quantitative instrument were processed using the Statistical Package for Social Sciences (SPSS) Version 2.0 software. Also, descriptive statistics such as frequency tables, simple percentages and graphic illustrations were used to analyse the quantitative data and research questions. The qualitative data collected from the IDIs were analysed using Nivivio analytical software. Four hypotheses were tested using Chi-square (X²). Findings in the study showed that avarice and peer pressure are the major factors that influence undergraduates’ involvement in cybercrime. Therefore, the study recommends that government and stakeholders should organise programmes that will equip the undergraduates with enriching skill-acquisition programmes during holidays and vacations; in order to re-channel their attention and energy from cybercrimes to more worthwhile lucrative money-making ventures.